Motivasi Mahasiswa Bimbingan dan Konseling dalam Berwirausaha - Yulianto, Yulianto (STKIP Muhammadiyah Pringsewu, 2018)
This study describes the motivation of STKIP Guidance and Counseling students Muhammadiayah Pringsewu in entrepreneurship. From the results of the research and discussion, some conclusions can be drawn that the first subject is entrepreneurship in selling Muslim clothing and equipment, the second subject is entrepreneurship in the field of selling food and beverages, and the third subject is entrepreneurship in the field of typing services. The three subjects in this study had different entrepreneurial motivations, DMS had a motive for self-development, ASP had an independence motive, and AL had a motive for income. Students who are self-employed are not for income reasons, the subject prioritizes the interests of their studies compared to the entrepreneur so that the subject does not pursue the income target for the entrepreneur this makes the subject able to undergo both activities together, namely study and entrepreneurial activities.Keywords:Â entrepreneurship, student motivation, guidance and counseling.